Сравнительная характеристика клеточного состава гемолимфы комнатной и синей падальной мух - Викторов-Набоков, О.В.; Корнеева, Л.А.; Харченко, Л.В.; Малеванная, З.А. (Вестник зоологии, 1977)
Six types of hemocytes were found in Musca domestica and Calliphora vicina hemo lymph: proleucocytes, macronucleocytes, micronucleocytes, trophic cells, phagocytes and enocytoids. M. domestica age III larvae and C. vicina chrysalises and prechrysalises pos sess the most complete set of hemocytes. In general the size of hemocytes of C. vicina is larger than that of M. domestica. Lack of protein food considerably changes the C. vicina hemolymph picture but does not effect the M. domestica hemolymph. Alterations in the hemolymph picture during ontogeny are similar for both species.